Industries and the bank lending effects of bank credit demand and monetary policy in Germany - Ivo J. M. Arnold; Clemens J. M. Kool; Katharina Raabe (Deutsche Bundesbank, 2006)
This paper presents evidence on the industry effects of bank lending in Germany and identifies the industry effects of bank lending associated with changes in monetary policy and industryspecific bank credit demand. To this end, we estimate individual bank lending functions for 13 manufacturing and non-manufacturing industries and five banking groups using quarterly bank balance sheet and bank lending data for the period 1992:1-2002:4. The evidence from dynamic panel data models shows that industry-specific bank lending growth predominantly responds to changes in industry-specific bank credit demand rather than to changes in monetary policy. In fact, conclusions regarding the bank lending effects of monetary policy are very sensitive to the choice of industry. The empirical results lend strong support to the existence of industry effects of bank lending. Because industries are a prominent source of variation in the bank lending effects of bank credit demand and monetary policy, the paper concludes that the industry composition of bank credit portfolios is an important determinant of bank lending growth and monetary policy effectiveness.
Keywords: G21; E52; L16; C23; 330; Monetary policy transmission; credit channel; industry structure; dynamic panel data; Geldpolitik; Transmissionsmechanismus; Kredit; Branche; Wirtschaftsstruktur; Schätzung; USA